2009
DOI: 10.1186/1471-2148-9-40
|View full text |Cite
|
Sign up to set email alerts
|

The extent of population genetic subdivision differs among four co-distributed shark species in the Indo-Australian archipelago

Abstract: Background: The territorial fishing zones of Australia and Indonesia are contiguous to the north of Australia in the Timor and Arafura Seas and in the Indian Ocean to the north of Christmas Island. The area surrounding the shared boundary consists of a variety of bio-diverse marine habitats including shallow continental shelf waters, oceanic trenches and numerous offshore islands. Both countries exploit a variety of fisheries species, including whaler (Carcharhinus spp.) and hammerhead sharks (Sphyrna spp.). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 47 publications
9
109
5
1
Order By: Relevance
“…Many of the species caught by the ECIFF were also identified by risk assessments as among the least likely to be sustainable across other northern Australia fisheries (Stobutzki et al 2002;Salini et al 2007) and are also probably affected to some extent by recreational fishing within the GBRWHA (Lynch et al 2010). Stocks of some species are known to be shared with other nearby jurisdictions, so unsustainable fishing practices in these areas would also potentially affect GBRWHA populations (Ovenden et al 2009), as would illegal fishing encroaching on northern Australian waters (Field et al 2009). In contrast to the threats posed by fishing, an integrated risk assessment for climate change of the GBRWHA suggested that most of the carcharhiniforms caught in the ECIFF were unlikely to have a high vulnerability to climate change owing to their high adaptive capacities (Chin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the species caught by the ECIFF were also identified by risk assessments as among the least likely to be sustainable across other northern Australia fisheries (Stobutzki et al 2002;Salini et al 2007) and are also probably affected to some extent by recreational fishing within the GBRWHA (Lynch et al 2010). Stocks of some species are known to be shared with other nearby jurisdictions, so unsustainable fishing practices in these areas would also potentially affect GBRWHA populations (Ovenden et al 2009), as would illegal fishing encroaching on northern Australian waters (Field et al 2009). In contrast to the threats posed by fishing, an integrated risk assessment for climate change of the GBRWHA suggested that most of the carcharhiniforms caught in the ECIFF were unlikely to have a high vulnerability to climate change owing to their high adaptive capacities (Chin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Each fin was allocated to a broad geographical origin (i.e. western Atlantic, eastern Atlantic, or Indo-Pacific) by matching its haplotype (by eye) to the geographic distribution of mtCR haplotypes obtained from the combined baseline genetic datasets of Duncan et al (2006), Ovenden et al (2009), and the present study (combined n = 452 wild-caught, globally distributed individuals). The evolutionary relationships of 'novel' market fin haplotypes not recorded in any of these 3 surveys to the known wild-caught haplotypes were assessed using a statistical parsimony network constructed in TCS 4.1 (Clement et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…not found in the global survey of Duncan et al 2006; GenBank accession numbers GU014389, GU014390 and GU014391). None of the western Atlantic haplotypes were recorded in the Indo-Pacific by Duncan et al (2006;n = 228) or Ovenden et al (2009;n = 47). Similarly, none of the Indo-Pacific haplotypes were recorded in our survey of western Atlantic animals.…”
Section: Western Atlantic Stock Structurementioning
confidence: 99%
“…sorrah, reserving C. sorrah for the subcluster that includes specimens from Indonesia. The existence of genetic differences between Australian and Indonesian specimens of C. sorrah was also noted by Ovenden et al (2009 A total of 98 specimens identified as C. limbatus were analyzed. These specimens span much of the reported global distribution of this species and include a diversity of localities throughout the Indo-Pacific (i.e., Philippines, Taiwan, Borneo, Vietnam, northern Australia, India, Madagascar, Gulf of California, and Hawaii), as well as several localities in the eastern Atlantic (i.e., Sierra Leone and South Africa) and a diversity of localities in the western Atlantic (including the Gulf of Mexico, Belize, and Puerto Rico).…”
Section: Carcharhiniformes (Ground Sharks)mentioning
confidence: 99%